2020
DOI: 10.3389/fphys.2020.597395
|View full text |Cite
|
Sign up to set email alerts
|

The Functional Availability of Arterial Kv7 Channels Is Suppressed Considerably by Large-Conductance Calcium-Activated Potassium Channels in 2- to 3-Month Old but Not in 10- to 15-Day Old Rats

Abstract: BackgroundVoltage-gated potassium (Kv) channels, especially Kv7 channels, are major potassium channels identified in vascular smooth muscle cells with a great, albeit differential functional impact in various vessels. Vascular smooth muscle Kv7 channels always coexist with other K channels, in particular with BK channels. BK channels differ in the extent to which they influence vascular contractility. Whether this difference also causes the variability in the functional impact of Kv7 channels is unknown. There… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…In addition to different expression levels, the functional impact of K v 7 channels depends on the activity of other potassium channels. A recent study demonstrated that BK Ca channel activity (which increases with age, see further in detail) suppresses K v 7 channel functional availability in saphenous arteries of adult, but not young, rats [46].…”
Section: The Vasomotor Role Of K V Channels Decreases With Maturationmentioning
confidence: 91%
See 3 more Smart Citations
“…In addition to different expression levels, the functional impact of K v 7 channels depends on the activity of other potassium channels. A recent study demonstrated that BK Ca channel activity (which increases with age, see further in detail) suppresses K v 7 channel functional availability in saphenous arteries of adult, but not young, rats [46].…”
Section: The Vasomotor Role Of K V Channels Decreases With Maturationmentioning
confidence: 91%
“…In rat cerebral arteries, the effects of BK Ca channel blockade became more pronounced with age-the BK Ca channel blocker, iberiotoxin, caused a contraction and an increase in the intracellular calcium concentration in arteries of adult (12-14 weeks old), but not newborn, rats (1-2 days old) [77]. Similarly, iberiotoxin led to an increase in basal tone and sensitivity to the α 1 -adrenoceptor agonist methoxamine in saphenous arteries of adult (2-3 months old), but not of young (10-15 day old), rats [45,46]. The effects of iberiotoxin on the contraction of sheep middle cerebral arteries also increased with age [40].…”
Section: The Vasomotor Role Of Bk Ca Channels Increases During Postnatal Developmentmentioning
confidence: 93%
See 2 more Smart Citations
“… 23 Importantly, these channels are active at more negative membrane potentials compared to other Kv channels making them perfect candidates for the K + current controlling the resting membrane potential of vascular smooth muscle cells. Over the past 20 years, a key role in vascular (and non‐vascular) smooth muscle has been established, with Kv7.4 and Kv7.5 channels predominating, 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 which are likely to be regulated by the ancillary subunit KCNE4. 5 , 33 , 34 Several reviews have summarized the evidence supporting an important role for Kv7.4 and Kv7.5 channels in vascular smooth muscle.…”
Section: Kv7 Channels In Vascular Smooth Musclementioning
confidence: 99%